The Relationship Between Premarital Reproductive Counselling and Husband Support with Increased Coverage Pure K1 Maternity Visit Coverage - Resmawati, Resmawati; Saputri, Chandra Ariani; Ariyana, Ariyana (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study aims to evaluate the relationship between premarital reproductive counseling and husband support with increased coverage of pure K1 pregnancy visits at Puskesmas Ajangale in 2022. Research Design and Methodology: This study used a correlation study design with a retrospective cohort approach. Secondary data were obtained from medical records and observational results, while primary data were collected through questionnaires. The study population consisted of first-trimester pregnant women who had their first contact with health workers at Ajangale Health Centre, and the sampling technique employed was total sampling. Findings and Discussion: The analysis results showed a significant correlation between premarital reproductive counseling and husband support, as well as increased coverage of pure K1 visits. Of the respondents who participated in premarital counseling, the majority made a pure K1 visit. Similarly, respondents who received good support from their husbands tended to be more compliant in conducting pure K1 visits. The P-value of 0.002 indicates a statistically significant association between these variables. Implication: This study confirms the importance of integrating premarital reproductive counseling programs in public health policies to increase the coverage of antenatal care visits. Husband support must also be improved through education and active involvement in antenatal care. The findings provide valuable insights for health practitioners and policymakers to improve maternal and child health.